The Description of Grammatical Errors in the Eighth Grade Students’ Descriptive Text of SMP Negeri 2 Gunungsitoli Utara in 2021/2022. - Yaredi Waruwu (Formosa Journal of Multidisciplinary Research, 2022)
Writing is one of the most difficult English skills. Therefore, many students who learn English as a foreign language tend to commit errors in their writings. Meanwhile, students are expected to be able to write English texts correctly. Based on the background of the problem, an analysis of grammatical errors is important to conduct. Therefore, the research was conducted with a qualitative descriptive design. It aims to describe the grammatical errors based on the types of omission, addition, misformation and misordering committed by the eighth grade students of SMP Negeri 2 Gunungsitoli Utara in 2021/2022. Furthermore, the data were collected from students’ descriptive writings. Finally, as the research findings, the type and percentage of grammatical errors committed by the students were omissions (58.82%), followed by misformation (29.41%), addition (8.82%), and misordering (2.94%). Thus, the results of this study can be used as a reference for students' writing problems at the school concerned.